Features of therapy selection in patients with glaucoma and “dry eye” syndrome - Zh.G. Oganezova; E.A. Egorov (РМЖ "Клиническая офтальмология")
J.G. Oganezova, E.A. Egorov Pirogov Russian National Research Medical University, Moscow, Russian Federation Along with the main focus of antiglaucomatous therapy — a reduction of IOP, there is a need to support the function of the optic nerve and retinal ganglion cells (RGC). In the prescription of neuroprotective therapy, the possibility of maintaining the functional activity of the RGC it should be considered primarily. Increased energy demand causes greater vulnerability of RGC in regulation violation of intracellular Ca2+, metabolic stress with increased IOP or vascular disorders. Currently, a toolkit of ophthalmologist has a variety of drugs for antihypertensive and neuroprotective therapy. In the presence of contraindications or insufficient effect of the first-choice drugs, it is switched to the second-choice drugs or combination therapy. In this situation, it is preferable to prescribe antiglaucomatous drugs with both pronounced antihypertensive and neuroprotective properties. Such drugs include a representative of selective alpha2-adrenergic agonists —brimonidine. In addition to neuroprotective effect, brimonidine has a double mechanism to reduce the level of IOP: at the same time, it reduces the production of water moisture and activates an uveoscleral outflow. 0.2% solution of brimonidine (Luxfen) contains in its formulation composition a moisturizing component — polyvinyl alcohol, due to which the problem of protecting the eye surface can be solved by prescribing more than one drug containing a preservative for a long period. Key words: POAG, neuroprotection, alpha-agonists, dry eye syndrome, brimonidine, Luxfen. For citation: Oganezova J.G., Egorov E.A. Features of therapy selection in patients with glaucoma and “dry eye” sydrome. RMJ “Clinical ophthalmology”. 2018;4:186–189.